2004
DOI: 10.1103/physrevb.69.224403
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the extraordinary Hall effect and resistivity

Abstract: We study the contribution of different types of scattering sources to the extraordinary Hall effect. Scattering by magnetic nano-particles embedded in normal-metal matrix, insulating impurities in magnetic matrix, surface scattering and temperature dependent scattering are experimentally tested. Our new data, as well as previously published results on a variety of materials, are fairly interpreted by a simple modification of the skew scattering model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 35 publications
2
30
0
1
Order By: Relevance
“…30 Experimentally, it has been found that the scattering at the surface, in the bulk, or at the interfaces contribute to AHE in different ways. The sign of surface scattering on AHE has been found to be same as that of the bulk in Ni films, 28,29 while it is opposite to that of the bulk or interface scattering in CoAg granular films 31 and Co/Pd multilayers. 27 To identify the specific contributions to AHE, a simple scaling relation between ρ AH and ρ xx is given by where the first term is related to the skew scattering and the second to the side jump.…”
Section: B Scaling Analysis Of Surface Scattering Effectmentioning
confidence: 89%
See 1 more Smart Citation
“…30 Experimentally, it has been found that the scattering at the surface, in the bulk, or at the interfaces contribute to AHE in different ways. The sign of surface scattering on AHE has been found to be same as that of the bulk in Ni films, 28,29 while it is opposite to that of the bulk or interface scattering in CoAg granular films 31 and Co/Pd multilayers. 27 To identify the specific contributions to AHE, a simple scaling relation between ρ AH and ρ xx is given by where the first term is related to the skew scattering and the second to the side jump.…”
Section: B Scaling Analysis Of Surface Scattering Effectmentioning
confidence: 89%
“…As n decreases to less than 20, ρ xx dramatically increases, which should be attributed to surface scattering. 28,29 Where the change of the sign of AHE from positive to negative is accompanied with a sharp increase in the absolute magnitude |ρ AH |. These phenomena indicate that (i) the sign of AHE for surface scattering is opposite to that of the bulk; it is positive for the bulk scattering, while negative for the surface scattering, and (ii) for the multilayers with n 20, ρ AH is dominated by surface scattering.…”
Section: A Magnetization and Magnetotransport Of The As-deposited Mumentioning
confidence: 94%
“…In general, experimental data does not fit well the predictions of the models. It was then suggested [20] that in systems with several different scattering sources, the total resistivity is not a good parameter to characterize the effect. Instead, both the EHE and resistivity should be decomposed to contributions generated by different scattering sources and the correlation for each source should be followed independently.…”
mentioning
confidence: 99%
“…Instead, both the EHE and resistivity should be decomposed to contributions generated by different scattering sources and the correlation for each source should be followed independently. Surfaces, impurities, and thermal scattering contributions, analyzed separately, were shown [20] to follow the skew scattering model regardless of the total material's resistivity. An additional mechanism connected with Berry phase and believed to take place in the absence of any scattering is also discussed [21].…”
mentioning
confidence: 99%
“…3,27 Recent experiments also suggested that magnons always give much smaller contribution to AHE in type of skew scattering than phonons. 28 Therefore, it is reasonable to consider the qualitative difference in various contributions to skew scattering and describe AHE resisitivity as…”
mentioning
confidence: 99%